Large-eddy simulation of separated turbulent flows over a three-dimensional hill using WRF and OpenFOAM. Issue 236 (May 2023) - Cao, Yong; Tao, Tao; Shi, Yujiang; Cao, Shuyang; Zhou, Dai; Chen, Wen-Li
Abstract: It is not clearly known about the limitations of the large-eddy simulation (LES) mode of an atmospheric model (WRF) in predicting the microscale flows for engineering purpose. This study chooses a typical separated turbulent flow past a three-dimensional axisymmetric hill and investigates the performance of WRF-LES in comparison with the popular CFD solver (OpenFOAM). The numerical models and conditions are set similarly between the two codes. The instantaneous visualization shows that both WRF-LES and OpenFOAM-LES can produce the primary flow features, including hairpin vortices, horseshoes, and surface-shear-induced vortices at different scales, with high similarity. Nevertheless, the turbulent kinetic energy in the near wake produced by WRF-LES is underestimated, in comparison with WRF-LES. The energy spectra suggest that WRF-LES using the high-order advection schemes has a stronger capacity of generating and maintaining small-scale turbulent motions than OpenFOAM-LES. Furthermore, the deviation of numerical dissipation behavior is examined between the two solvers. Highlights: Separated turbulent flows over a 3D hill are simulated by the atmospheric model WRF. WRF-LES performance is examined by OpenFOAM-LES when numerical setups are similar. WRF-LES produces a later flow separation and shear-layer instability. WRF-LES outperforms OpenFOAM-LES in reproducing small-scale motions in the far wake. Deviation of numerical dissipation behavior is examined between the two solvers.